The modulatory effects of irisin on asprosin, leptin, glucose levels and lipid profile in healthy and obese male and female rats - Ozcan, Sibel; Ulker, Nazife; Bulmus, Ozgur; Yardimci, Ahmet; Ozcan, Mete; Canpolat, Sinan (Taylor & Francis Ltd, 2022)
Objectives: The main aim of this study was to investigate the effects of irisin on asprosin, leptin, glucose levels and lipid profile in healthy and obese male and female rats. Methods: Irisin was subcutaneously administered with osmotic minipumps at the dose of 100 ng/kg/day for 28 days and then, the serum levels of asprosin, leptin, glucose and lipid profile were investigated. Results: Irisin infusion increased asprosin levels in male rats (p = .02) but not in female rats. Irisin inhibited obesity-induced high glucose, low-density lipoprotein (LDL), triglyceride (TG) and leptin levels in all groups; however, it did not lead to any change in asprosin levels in both obese female and male rats. Conclusions: It was determined that irisin increased serum asprosin levels and decreased LDL, TG, glucose and leptin levels, and this could indicate a protective role of irisin against obesity development.
Keywords: Irisin; asprosin; leptin; obesity